2001
DOI: 10.1016/s0005-2736(01)00362-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cell transfection with plasmid/chitosan complexes

Abstract: Chitosan is useful as a non-viral vector for gene delivery. Although there are several reports supporting the use of chitosan for gene delivery, studies regarding effects on transfection and the chitosan-specific transfection mechanism remain insufficient. In this report, the level of expression with plasmid/chitosan was observed to be no less than that with plasmid/lipofectin complexes in SOJ cells. The transfection mechanism of plasmid/chitosan complexes as well as the relationship between transfection activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
195
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(210 citation statements)
references
References 38 publications
14
195
0
1
Order By: Relevance
“…Chitosan is a versatile biomaterial derived from the exoskeleton of many crustaceans which can be used in the formulation of microparticles and nanoparticles suitable for drug delivery [15][16][17][18][19]. The amine groups on the chitosan chain are positively charged and can bind to negatively charged DNA and condense it into positively charged nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a versatile biomaterial derived from the exoskeleton of many crustaceans which can be used in the formulation of microparticles and nanoparticles suitable for drug delivery [15][16][17][18][19]. The amine groups on the chitosan chain are positively charged and can bind to negatively charged DNA and condense it into positively charged nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…According to some authors, the presence of serum enhances the transfection efficiency of Ch based polyplexes [41,67,68]. The reason for the increment of transfection in the presence of serum is not clear.…”
Section: Factors Involved In the Transfection Efficiency Of Lmwc Basementioning
confidence: 99%
“…Other studies have shown an association between surface charge and increased transfection efficiency as well as a decrease in toxicity [24,25]. Also, cellular uptake is one of the major obstacles for a successful gene delivery strategy and polyplexes are thought to enter the cell via endocytosis in a process that may be dependent on polyplex charge [26]. A higher surface charge can facilitate electrostatic interactions with the negatively charged proteoglycans in cellular membranes and hence promote polyplex internalization [27].…”
Section: Transfection Efficiency Is Formulation-dependentmentioning
confidence: 99%